2021
DOI: 10.17749/2077-8333/epi.par.con.2021.051
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological predictors of heart rate and conductivity disorders in juvenile myoclonic epilepsy

Abstract: Juvenile myoclonic epilepsy (JME) is the most common form of genetic generalized epilepsy. Patients with JME are at risk of life-threatening heart rhythm and conduction disorders as well as sudden death syndrome due to several potential mechanisms: genetic, clinical, neuroanatomical, pharmacological, psychological, comorbid. This lecture reviews important elements of knowledge about the pharmacological predictors of cerebral-cardiac syndrome and sudden unexpected death in epilepsy. The arrhythmogenic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…The problem of drug-induced LQTS was a discussion topic at the 2005 International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH). This led to the adoption and publication of recommendations on the evaluation of elongation QT interval and proarrhythmic potential of non-antiarrhythmic drugs (ICH-E14) [86,87]. The study concluded that almost all APs, with a few exceptions, should undergo a "thorough QT study" (TQT), as defined by ICH-E14.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The problem of drug-induced LQTS was a discussion topic at the 2005 International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH). This led to the adoption and publication of recommendations on the evaluation of elongation QT interval and proarrhythmic potential of non-antiarrhythmic drugs (ICH-E14) [86,87]. The study concluded that almost all APs, with a few exceptions, should undergo a "thorough QT study" (TQT), as defined by ICH-E14.…”
Section: Discussionmentioning
confidence: 99%
“…The latter group was further subdivided into class B* drugs (Table 5). APs that are best avoided in patients with congenital QT interval prolongation, with a conditional risk of TdP, and those with a known risk of TdP were compiled into class B* [2,87,88]. LQTS is an important risk factor for the development of TdP, which, in turn, can lead to ventricular fibrillation and SDS [89].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations